Reduced murine double minute-2 methylation from peripheral blood mononuclear cells correlates with enhanced oxidative stress in hepatitis b virus-related hepatocellular carcinoma - Jing-Wen Wang; Han-Xu Zhu; Feng Zhang; He Wang; Yu-Chen Fan; Yu-Chen Fan; Li-Yan Han; Kai Wang; Kai Wang (Frontiers in Microbiology)
BackgroundHepatitis B virus-related hepatocarcinogenesis (HBV-related HCC) involves a variety of causes including oncogene hypomethylation, oxidative stress and HBV itself. Oxidative stress induces an alternation in the DNA methylation status. We aimed to study the relationship between oxidative stress and murine double minute-2 (MDM2) methylation status in HBV-related HCC patients and healthy controls (HCs).MethodsA total of 135 patients with HBV-related HCC and 26 healthy controls (HCs) were recruited. The MDM2 methylation status was detected by methylation-specific PCR. The expression of MDM2 mRNA was assessed using quantitative real-time PCR. The plasma malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), nuclear factor erythroid 2-related factor 2 (NRF2), heme Oxygenase-1 (HO-1), and glutathione peroxidase 4 (GPX4) were measured by enzyme-linked immunosorbent assay (ELISA). Thirty-six patients with HBV-related HCC and 11 HCs were selected and the serum metabolism was analyzed by ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS).ResultsCompared with HCs, the MDM2 promoter methylation frequency was significantly decreased in HBV-related HCC. The MDA levels were increased, whereas the GSH, SOD, NRF2, HO-1, and GPX4 levels were decreased in the HBV-related HCC patients relative to HCs. There were 216 differential metabolites between HBV-related HCC and HCs in plasma, which belongs to amino acids, bile acids, fatty acids, phospholipids, and other compounds. The cysteine and methionine metabolism were the most significant metabolic pathways associated with differential metabolites between MDM2 methylated group and MDM2 unmethylated group in HBV-related HCC.ConclusionOur results suggested that oxidative stress may cause MDM2 hypomethylation, in which cysteine and methionine pathway might play an important role in.